The Investigation of Thermal and Magnetic Properties and Microstructure Analysis of Cu-Al-Mn Shape Memory Alloys - Canbay, Canan Aksu; Aydogdu, Ayse; Aydogdu, Yildirim (Springer, 2011)
In this study, the transformation temperatures and shape memory effect of Cu-Al-Mn shape memory alloys were investigated by calorimetric measurements. Cu-Al-Mn alloys in the range of 10-15 wt% of aluminum and 0-10 wt% of manganese; exhibiting beta-phase at high temperatures, were prepared. With an increase in the aluminum and manganese concentrations of the alloy, the martensite morphology is modified and the transformation temperatures are decreased. The activation energies of the alloys were calculated according to the Ozawa and Kissinger methods. Magnetic properties of the alloys were studied and it was seen that the alloys show low magnetization. The microstructures of the alloys were investigated by optical micrographs where the martensite variants with different orientations can be observed from the micrographs.
Keywords: Shape memory alloy; Transformation temperatures